Comparison of the antioxidant capacity in cold-treated recombinant wheat lines - Soltész, Alexandra (Acta Biologica Szegediensis, 2005)
In earlier experiments using 5A chromosome substitution lines of wheat with different freezing tolerance it was shown that this chromosome plays an important role in the regulation of cold-induced changes in the level of antioxidant enzymes and thiols. The purpose of our experiments was to determine the region of chromosome 5A where the genes responsible for the control of stress-induced changes in the level of the antioxidants are localised. Activities of antioxidant enzymes and the glutathione synthesis were compared in lines recombinant for the long arm of chromosome 5A. The chromosome region between the markers Xpsr805 and Xpsr164 was found to influence the cold-induced changes in hydroxymethylglutathione and glutathione levels. The glutathione reductase activity may be affected by the chromosome region near to the marker B-amy-A1.